The Influence Of Live Streaming Using The Soft Selling Method On The Purchase Interest Of Thrift Fashion Products Among Gen Z In Bengkulu City - Sadewo, Panji; Hanila , Siti; Febliansa , M Rahman (Journal of Business Management, 2025)
This study aims to analyze the influence of Feeling (X₁), Implicit (X₂), and Brand Image (X₃) on Purchase Intention of Thrift Fashion Products (Y) among Generation Z in Bengkulu City. The research employs a quantitative descriptive method with a multiple linear regression approach, based on data from 150 respondents aged 17–28 years, processed using SPSS version 25.0. The results indicate that all questionnaire items are valid (r-count > 0.160) and reliable, with Cronbach’s Alpha values for each variable as follows: Feeling (0.911), Implicit (0.906), Brand Image (0.925), and Purchase Intention (0.892). The partial test (t-test) shows that all independent variables have a positive and significant effect on purchase intention, with t-count and significance values respectively: Feeling (8.241; Sig. = 0.000), Implicit (3.074; Sig. = 0.003), and Brand Image (20.405; Sig. = 0.000). Among these variables, Brand Image is the most dominant factor, with a standardized beta value of 0.610. The simultaneous test (F-test) reveals that the three variables jointly have a significant effect on Purchase Intention, with an F-count value of 1253.047 and Sig. = 0.000 (<0.05). The coefficient of determination (R²) of 0.963 indicates that 96.3% of the variation in Purchase Intention can be explained by the variables Feeling, Implicit, and Brand Image, while the remaining 3.7% is influenced by other factors outside the model such as price, product quality, influencer promotion, and social trends. This study concludes that emotional factors, subconscious perceptions, and brand image collectively play an important role in increasing purchase intention for thrift fashion products. Therefore, strengthening brand image, creating positive emotional experiences, and implementing subtle yet effective soft selling strategies are key to attracting Generation Z’s interest in sustainable products.